Cutaneous Larva migrans: A Case Series of a Skin-related Neglected Tropical Diseases from Nepal - Shrestha, Shraddha; Hirachan, Shashi; Parajuli, Niraj (Journal of Nepal Health Research Council, 2024)
Cutaneous larva migrans is a tropical dermatosis acquired through the helminthic infection. It is caused by penetration of animal hookworm larva in patient with history of walking barefoot on soil or beaches or with history of travel to tropical areas. It usually presents clinically as a pruritic serpiginous lesion with a trailing. Here, we report three cases who presented as asymptomatic to pruritic thread like serpiginous lesion on cutaneous examination. Cutaneous larva migrans was diagnosed clinically and proper treatment was done with complete regression of manifestations within a week. Although the condition is self-limiting, it is an under-diagnosed entity leading to delay in treatment and exacerbation of clinical manifestations including rare pulmonary manifestation called Loefflers syndrome. Keywords: Creeping eruption; ivermectin; larva migrans; skin-NTDs.